A new species of the genus Octomeria (Orchidaceae: Pleurothallidinae) from Ecuador - Vélez-Abarca, Leisberth; Iturralde, Gabriel A.; Garzón, Henry X.; Gutiérrez Del Pozo, Diego; Baquero, Luis E. (Phytotaxa, 2024)
A new species of Octomeria was found during an orchid research expedition in the southern Ecuadorian Amazon. Octomeria jimenezii is described and illustrated, and information on its distribution, habitat and conservation status is provided. The newly proposed taxon is morphologically similar to O. pacii, from which it differs by the lower lateral lobes, with an obtuse to subacute angle to the anterior margin.